H1N1 Influenza: Assessment of knowledge and awareness of private dental health professionals of a Tricity - Singh, Iqbal (J Family Med Prim Care, 2019)
BACKGROUND: Influenza like Swine flu virus has posed a greater risk of occupational transmission to dental professionals as it can spread through the aerosols. AIM: To assess knowledge and awareness of private dental health care professionals regarding swine flu of a Tricity in India. MATERIALS AND METHODS: A cross-sectional study was conducted among 255 private dentists practising in the Tricity. A self-administered, anonymous, multiple choice type questionnaire was administered to gather information. The questionnaire contained 12 questions on knowledge and awareness regarding swine flu keeping in view the time constraints. Statistical analysis was done using ANOVA and student t-test. RESULTS: Awareness regarding mode of transmission of swine flu were reported positively by 88.5% of subjects. About 24.6% of subjects reported about having encountered a swine flu patient at their clinic. Preventive measures to prevent spread of swine flu were known to 71.2% of subjects. Statistically significant association of mean knowledge scores was noted with education level (P = 0.015) and working profile (P = 0.017) of the subjects. CONCLUSION: The results of the present review showed that some knowledge gaps existed among dentists regarding some important aspects of swine flu. Therefore, there is an urgent need for training and continuous education programs regarding infectious diseases.